The energy resources of Central Asia and their impact on inter-state relations (Journal of Oriental Studies, 2016)
This article investigates the role of energy resources in Central Asia in international relations. In the past decade energy resources of Central Asia have become an objective of keen and competitive struggle between the key consuming countries. Moreover, the region under question is becoming one of the foreign policy priorities for the transatlantic community.
Keywords: power resources; post-Soviet